Profiling of m6A RNA modifications identified an age‐associated regulation of AGO2 mRNA stability. Issue 3 (23rd March 2018) - Min, Kyung‐Won; Zealy, Richard W.; Davila, Sylvia; Fomin, Mikhail; Cummings, James C.; Makowsky, Daniel; Mcdowell, Catherine H.; Thigpen, Haley; Hafner, Markus; Kwon, Sang‐Ho; Georgescu, Constantin; Wren, Jonathan D.; et al.
Summary: Gene expression is dynamically regulated in a variety of mammalian physiologies. During mammalian aging, there are changes that occur in protein expression that are highly controlled by the regulatory steps in transcription, post‐transcription, and post‐translation. Although there are global profiles of human transcripts during the aging processes available, the mechanism(s) by which transcripts are differentially expressed between young and old cohorts remains unclear. Here, we report on N6‐methyladenosine (m6A) RNA modification profiles of human peripheral blood mononuclear cells (PBMCs) from young and old cohorts. An m6A RNA profile identified a decrease in overall RNA methylation during the aging process as well as the predominant modification on proteincoding mRNAs. The m6A‐modified transcripts tend to be more highly expressed than nonmodified ones. Among the many methylated mRNAs, those of DROSHA and AGO2 were heavily methylated in young PBMCs which coincided with a decreased steady‐state level of AGO2 mRNA in the old PBMC cohort. Similarly, downregulation of AGO2 in proliferating human diploid fibroblasts (HDFs) also correlated with a decrease in AGO2 mRNA modifications and steady‐state levels. In addition, the overexpression of RNA methyltransferases stabilized AGO2 mRNA but not DROSHA and DICER1 mRNA in HDFs. Moreover, the abundance of miRNAs also changed in the young and old PBMCs which are possibly due to a correlation with AGO2 expression as observed in AGO2‐depleted HDFs. Taken together, we uncovered the role of mRNA methylation on the abundance of AGO2 mRNA resulting in the repression of miRNA expression during the process of human aging.